Laboratory effluent Treatment by Using Coagulant Alum sulphate and Poly Aluminium Chloride (PAC) - Raimon Raimon; Muhammad Said (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
It has been investigated of the laboratory effluent treatment using coagulant Alum sulphate (AS) and Poly Aluminum Chloride (PAC). This research purposes to get the best doses of coagulant in waste water treatment. Parameter focuses are Total Dissolved Solid (TDS), Fe, Mn, Cr, and Ammoniac (NH3). The result shows the Alum sulphate was more effective. The effectiveness of pollutant decrease is 58,80% of TDS, 99,14% of Fe, 98% of Cr, 77,24% of Mn, and 23,18% of Ammoniac, respectively.Keywords: Laboratory wastewater, Alum sulphate, Poly Aluminum Chloride, Heavy metals, Coagulation